El uso de las tics para el mejoramiento de la atención - Espinoza Olaya, Lady Carolina (Machala, Universidad Técnica de Machala, 2023)
Attention problems in educational contexts have become a problem that is increasing worldwide, significantly damaging the teaching and learning processes. In this sense, it is important to look for psycho-pedagogical strategies that allow us to intervene in this situation in a timely manner. With the above in this work, the following general objective was raised to improve care for boys and girls in the sixth year of basic general education at Esc. “Lcdo. Alonso Campoverde Campoverde, through the implementation of a guide of psycho-pedagogical activities with the use of Tics. This work is assisted by a qualitative research, with a qualitative paradigm using techniques such as observation, structured interview was important when collecting and storing data in relation to the attention problems of children, the use of methods historical-logical and analytical-synthetic allowed to strengthen the investigation. The interviews applied to the teachers in their classroom context made it possible to show that they are unaware of strategies to address students with attention problems, they explain that they apply what they learned in their training stage and what they have been able to train in some courses, making it difficult for them generate management strategies for this problem. The implementation of a proposal framed in a guide of psycho-pedagogical activities through the use of Tics to improve the attention of sixth-year students will attract attention and energize teaching processes, facilitating the work of teachers.
Los problemas de atención en los contextos educacionales se han convertido en una problemática que se acrecienta a nivel mundial perjudicando de manera notoria los procesos de enseñanza y de aprendizaje. En este sentido es importante buscar estrategias psicopedagógicas que permitan intervenir de manera oportuna esta situación. Con lo anteriormente expuesto en este trabajo se planteó el siguiente objetivo general mejorar la atención en niños y niñas de sexto año de educación general básica de la Esc. “Lcdo. Alonso Campoverde Campoverde, mediante la implementación de una guía de actividades psicopedagógicas con la utilización de las Tics. Este trabajo se asiste de una investigación de tipo cualitativa, con un paradigma cualitativo utilizando técnicas como la observación, entrevista estructurada fue importante a la hora de recolectar y almacenar datos en relación a los problemas de atención de los niños y niñas, la utilización de métodos histórico-lógico y analítico- sintético permitieron fortalecer la investigación. Las entrevistas aplicadas a las docentes en su contexto áulico permitieron evidenciar que desconocen de estrategias para abordar estudiantes con problemas de atención, ellos explican que aplican lo que aprendieron en su etapa de formación y lo que se han podido capacitar en algunos cursos, dificultándoles de manera significativa generar estrategias de manejo para esta problemática. La implementación de una propuesta enmarcada en una guía de actividades psicopedagógicas mediante la utilización de las Tics para mejorar la atención de estudiantes de sexto año permitirá captar la atención y dinamizan los procesos de enseñanza facilitando el trabajo de los docentes.
Keywords: Atención; Actividades; Tics; Enseñanza